Once upon a time in Malaysia interloper - Davendralingam Sinniah (Bluetoffee Pte Ltd, 2019)
A romance novel, the plot revolves around the experiences of the main character, a British woman named Nicola whose arrival in then-Malaya takes a dangerous turn when she falls into the hands of pirates.